Framework of Systematic Sustainability Assessment Strategy (FSSAS) for Hydroelectric Power Industry in Malaysia - Kartina, Johan; Faiz, Mohd Turan (IOP Publishing, 2017)
Hydroelectric power is an alternative power resource in Malaysia and always associated with negative impact on environmental, social and economy of the surrounding site. The dispute over environmental, societal and economic issues can be minimised if compliance to sustainability development requirement is included in the project as part of the project premises during planning phase. This paper suggests a framework targeted for decision-makers in charge of implementing the projects to produce hydropower the sustainable way in Malaysian context which can mitigate the risks in social, environment and economy. The framework is strategic in nature and based on project management methodology with objective to provide a 'common language' by having a project value as measureable for stakeholders to state their mutual agreement of what a sustainable hydropower project in the context of Malaysia and in line with the United Nations (UN) 17 Sustainable Development Goals (SDGs). The paper discusses how the proposed systematic sustainability assessment strategy (FSSAS) framework support the call for Malaysia to promote meaningful public participation in ensuring land and natural resource decisions and to address citizens' interests which is the core idea of Environmental Democracy Index established in 2014. The paper argues that, even though it is at present impossible to define precision status of sustainability development with respect to the nature of the multi stakeholders and the lack of systematic assessment the proposed FSSAS framework can be a valuable tool because it tracks the project value as a quantitative deliverable to determine the status of the journey in sustainable development towards accomplishing the SDG under a consensus in hydropower industry of any scale over time.